Robust assessment of tumor mutational burden in cytological specimens from lung cancer patients. (November 2020) - Alborelli, Ilaria; Bratic Hench, Ivana; Chijioke, Obinna; Prince, Spasenija Savic; Bubendorf, Lukas; Leuenberger, Laura P.; Tolnay, Markus; Leonards, Katharina; Quagliata, Luca; Jermann, Philip; Matter, Matthias S.
Highlights: TMB is a promising predictive biomarker for immune checkpoint inhibitor response. Many lung cancer samples are limited to cytological material. TMB measurement on cytological smears has not been evaluated yet. We observed robust TMB measurement in cytological smears. Cytological smears should be preferred to formalin-fixed tissue samples. Abstract: Objectives: Tumor mutational burden (TMB) has emerged as a promising predictive biomarker for immune checkpoint inhibitor therapy. While the feasibility of TMB analysis on formalin-fixed paraffin-embedded (FFPE) samples has been thoroughly evaluated, only limited analyses have been performed on cytological samples, and no dedicated study has investigated concordance of TMB between different sample types. Here, we assessed TMB on matched histological and cytological samples from lung cancer patients and evaluated the accuracy of TMB estimation in these sample types. Materials and Methods: We analyzed mutations and resulting TMB in FFPE samples and matched ethanol-fixed cytological smears (n = 12 matched pairs) by using a targeted next-generation sequencing assay (Oncomine™ Tumor Mutational Load). Two different variant allele frequency (VAF) thresholds were used to estimate TMB (VAF = 5% or 10%). Results: At 5% VAF threshold, 73% (107/147) of mutations were concordantly detected in matched histological and cytological samples. Discordant variants were mainly unique to FFPE samples (34/40 discordant variants) and mostly C:G > T:A transitions with low allelic frequency, likely indicating formalin fixation artifacts. Increasing the VAF threshold to 10% clearly increased the number of concordantly detected mutations in matched histological and cytological samples to 96% (100/106 mutations), and drastically reduced the number of FFPE-only mutations (from 34 to 4 mutations). In contrast, cytological samples showed consistent mutation count and TMB values at both VAF thresholds. Using FFPE samples, 2 out of 12 patients were classified as TMB-high at VAF cutoff of 5% but TMB-low at 10%, whereas cytological specimens allowed consistent patient classification independently from VAF cutoff. Conclusion: Our results show that cytological smears provide more consistent TMB values due to high DNA quality and lack of formalin-fixation induced artifacts. Therefore, cytological samples should be the preferred sample type for robust TMB estimation.